2007
DOI: 10.1001/archderm.143.8.1007
|View full text |Cite
|
Sign up to set email alerts
|

Age- and Site-Specific Variation in the Dermoscopic Patterns of Congenital Melanocytic Nevi

Abstract: To describe the dermoscopic features of congenital melanocytic nevi (CMN) and assess whether predominant dermoscopic patterns present in CMN are related to an individual's age ( Ͻ12 years vs Ն12 years), sex, or lesional site (head, neck, and trunk vs extremities).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
56
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 31 publications
14
56
2
1
Order By: Relevance
“…The predominant patterns of all melanocytic nevi were globular (50 %), consistent with prior studies [7]. They also observed a reticular pattern among nevi present at birth (28 %), which contradicts previous descriptions of a predominately reticular pattern in CMN for individuals 12 years or older [7,8]. The presence of both globular and reticular patterns in CMN raises questions regarding nevus evolution and pathways responsible for nevogenesis.…”
Section: Congenital Melanocytic Nevisupporting
confidence: 76%
“…The predominant patterns of all melanocytic nevi were globular (50 %), consistent with prior studies [7]. They also observed a reticular pattern among nevi present at birth (28 %), which contradicts previous descriptions of a predominately reticular pattern in CMN for individuals 12 years or older [7,8]. The presence of both globular and reticular patterns in CMN raises questions regarding nevus evolution and pathways responsible for nevogenesis.…”
Section: Congenital Melanocytic Nevisupporting
confidence: 76%
“…Of note is the fact that the number of these vessels in the lesion may not be very many and thus may be referred to as lonely arborising vessels that may traverse the length of the lesion. The finding of yellowish white structureless areas to globules on dermoscopy is similar to the milia like cysts that have been described as variously sized white or yellowish structures in seborrhoeic keratoses and congenital melanocytic nevi [2][3][4].…”
supporting
confidence: 75%
“…In a recently published work, Changchien et al[ 14] observed additional dermoscopic features in CMN which they added to those proposed by Seidenari and Pellacani [1] and Seidenari et al [2, 3]: the milia-like cysts (characteristic dermoscopic finding of seborrheic keratosis) and the haloed globules , which are globules surrounded by a hypopigmented halo. The authors structurally differentiated haloed globule from target globule, which was initially described by Seidenari et al as a clear globule containing a central dot.…”
Section: Discussionmentioning
confidence: 87%